Leadership Core Competencies in Palliative Care-Recommendations from the European Association for Palliative Care: Delphi Study - Parczyk, Olivia; Frerich, Gerrit; Loučka, Martin; Voltz, Raymond; Payne, Sheila (Journal of palliative medicine, 2024)
Background: Leadership competencies are essential for the future development of the field of palliative and hospice care. However, a consensus on the core competencies of good leadership is not yet available. Objective: To elicit consensus on core leadership competencies in palliative care. Design: Based on a literature review, a list of 119 specific leadership competencies was compiled. Subsequently, a Delphi technique used three online survey rounds and a final expert consultation (the board of the European Association for Palliative Care [EAPC]) to assess the importance of these competencies. Setting/Participants: International experts in leadership in palliative care were identified from an online search and EAPC networks. Results: From the 194 international multiprofessional experts invited to participate, 99/78/64 took part in the 3 rounds. One hundred fifteen items from eight domains of leadership (research, advocacy and media, communication, teamwork, project management, organizational learning and sustainability, leading change, and personal traits) reached consensus and were deemed as important. Conclusions: The eight domains provide evidence for teaching of leadership competencies in palliative care. We recommend that exploring, identifying, and integrating leadership competencies in palliative care are given more attention in educational curricula and in training interventions.
Keywords: leadership; palliative care; vůdcovství; komunikace; delfská metoda; paliativní péče; Humans; Palliative Care; Delphi Technique; Leadership; Communication; Consensus; education; Delphi technique; lidé; konsensus; consensus